The Use of Discovery Learning Method to Teach Reading Narrative Text - Khairunnisa, Khairunnisa; Rosnija, Eni; Surmiyati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The aim of this study is to find out the effectiveness of discovery learning method for teaching reading comprehension to the ninth-grade students of SMPN 11 Pontianak in academic year 2023/2024 and how effective the discovery learning method is. This research used a quasi-experimental method with measurement data collection technique. The instruments used were tests and observation checklists. The population was all ninth grade students and the sample was taken using convenience sampling techniques. The experimental group was class 9F with 32 students and the control class was 9E with 31 students. The findings showed that discovery learning can improve students' reading comprehension of narrative text abilities. The post-test score was 87.23 which was higher than the pre-test score 63.23. Further, the effect size of the treatment was 0.781 which indicates the discovery learning method has a moderate effect. Additionally, the environment in the classroom also becomes more active according to the result of the observation checklist. The alternative hypothesis of this research is accepted. In short, the use of discovery learning method is effective in teaching reading comprehension of narrative text on ninth grade students of SMPN 11 Pontianak in Academic year 2023/2024. Therefore, the researcher suggest that the discovery learning method can be implemented to teach reading narrative text.